SOSIALISASI PROGRAM PEACE EDUCATION PADA SISWA SEKOLAH DASAR: The Socialization of Peace Education Program on Elementary School Students - Ivanisari, Aji Ria Finola; Utomo, Setiyo (Program Studi Sastra Indonesia Universitas Mulawarman, 2025)
Abstract: Indonesia's capital city, which will move to Penajam Paser Utara in 2024, is directly connected to the Kampung Lama area, Samboja. The method used is socialization by implementing games to elementary school students. It is undeniable that there will be many immigrants filling this area with different racial and ethnic backgrounds. This makes conflicts prone to occur, especially in the past there has been a Sampit War involving two different tribes. Therefore, Peace Education is relevant and must be introduced to children of the younger generation as an effort to reconstruct today's social society. The results of community service through Peace Education have a good impact on understanding the resolution of conflicts that occur in the future so that this program becomes part of social reconstruction of conflicts that occur in the future. Elementary school students' understanding of conflict prevention can be minimized with games in the socialization of the Peace Education program. Keywords: Peace Education; Social Society; Conflict Abstrak: Ibu Kota Negara Indonesia yang akan pindah di Penajam Paser Utara pada tahun 2024 terhubung langsung dengan wilayah Kampung Lama, Samboja. Adapun metode yang digunakan adalah sosialisasi dengan mengimplementasikan permainan pada siswa sekolah dasar. Tidak dipungkiri nantinya akan ada banyak pendatang mengisi wilayah ini dengan latar belakang ras dan suku yang berbeda. Ini menjadikan konflik rawan terjadi, terlebih di masa lalu telah terjadi Perang Sampit yang melibatkan dua suku berbeda. Oleh karena itu, Peace Education menjadi relevan dan harus dikenalkan pada anak-anak generasi muda sebagai upaya untuk merekonstruksi masyarakat sosial saat ini. Hasil pengabdian kepada Masyarakat melalui Peace Educationmemberikan dampak yang baik terhadap pemahaman atas penyelesaian konflik yang terjadi dikemudian hari sehingga program ini menjadi bagian dalam rekonstruksi sosial terhadap konflik yang terjadi dikemudian hari. Pemahaman siswa sekolah dasar terhadap pencegahan konflik dapat diminimalisir dengan permainan dalam sosialisasi program Peace Education. Kata kunci: Pendidikan Perdamaian; Masyarakat Sosial; Konflik